Bank Regulations and Credit Risk of Nepalese Commercial Banks - Bhattarai, Dhundi Raj; Sharma, Bhanu Bhakta; Pandeya, Churamani (NCC Journal, 2024)
Purpose of this study is to measure the impact of banking regulations specifically base rate, weighted average spread rate, bank capital, loan loss reserve, and broad money supply on credit risk of commercial banks in Nepal. Descriptive, correlational, and casual comparative research design have been used in this study. This study is based on secondary sources of data. Data were collected from annual audit reports of twenty- six commercial banks from fiscal year 2012/13 to 2018/19 out of twenty- seven, and from fiscal year 2020 to 2022, nineteen commercial banks out of twenty. Rastriya Banijya Bank (RBB) as a Government owned bank has been excluded in this study. The mean, range, standard deviation, coefficient of variation, correlation analysis, and multiple regression analysis statistical tools were used in this study. This study reveals that loan loss reserve is highly scattered than after bank capital, credit risk, broad money supply, base rate, and weighted average spread rate respectively. There is significant positive relationship of credit risk with bank capital, loan loss reserve, and broad money supply. Study results revealed that there is significant impact of bank capital, loan loss reserve, broad money supply, and base rate on credit risk.